ANKYLOSING SPONDYLITIS AND PREGNANCY: DATA FROM A PILOT STUDY BASED ON A QUESTIONNAIRE SURVEY OF PATIENTS - Z. M. Gandaloeva; O. A. Krichevskaya; T. V. Dubinina; N. M. Kosheleva; Sh. F. Erdes (Научно-практическая ревматология, 2018)
Objective: to clarify pregnancy outcomes in patients with ankylosing spondylitis (AS) and its course during pregnancy on the basis of a retrospective analysis.Subjects and methods. The paper presents the results of Stage 1 of a Russian pilot study of the impact of pregnancy on AS activity, parity, and pregnancy outcomes in these patients. The basis for Stage 1 is the results of a retrospective analysis of the data of a questionnaire survey of 204 women with AS, during which they answered 19 questions regarding the presence of pregnancies and their outcomes, the reasons for the lack of pregnancies, and a subjective assessment of their health status during gestation. The respondents’ mean age was 32.0±5.8 years; the mean disease duration was 107.2±73.5 months.Results and discussion. 84 (41.1%) women did not have pregnancies; the reasons for the lack of pregnancies were associated with AS (fear of the teratogenic effect of taken drugs; a child’ inheritance of the disease) in 48.8% of the cases, with infertility in 9.5%, and with non-medical reasons in 41.7%. A total of 120 (58.9%) women had 248 pregnancies; of whom 136 patients had the latter before and 112 – after the onset of AC. In AS versus a healthy life period, there were lower abortion rates at a woman’s will (8.9 and 35.3%, respectively; p < 0.01), more pregnancies that resulted in childbirth (75.9 and 52.2%, respectively; p < 0.01), and higher surgical delivery rates (43.5 and 28.2%, respectively; p < 0.05). The premature birth rate after the onset of AC was 13.0%. The newborn infants born before the onset of AS in mothers did not differ from those born after the onset of AS in mothers in weight and Apgar scores. Half of the respondents reported that their health status was improved in any trimester of pregnancy (slightly more often in the first trimester; but the difference was statistically insignificant). However, almost 70.0% of the respondents noted their worse health status during pregnancy, the severity of AS symptoms increased with a gestational period.Conclusion. The reason for the lack of pregnancies in almost half of the patients with AS is associated with their subjective fear of the negative impact of the disease and therapy on a child’s future health. In AS versus a healthy life period, surgical deliveries are performed more frequently. The neonatal outcomes of pregnancies do not differ before and after the onset of AS.